A Review of the Therapeutic Effects of Garlic in Lowering Blood Pressure: A Comprehensive Analysis of Recent Mechanisms and Existing Clinical Data - Hamdi, Ibnati Amira; Panggabean, Ridha Inayah; Theresa, Cindy Calista; Nainggolan, Bahagia Willibrordus Maria; Balatif, Ridwan (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Hypertension is a medical condition characterized by an elevation in systolic blood pressure equal to or greater than 140 mmHg and/or diastolic blood pressure equal to or greater than 90 mmHg. Hypertension elevates the likelihood of developing cerebrovascular disease and mortality. The administration of conventional antihypertensive drugs frequently leads to the occurrence of adverse effects. Moreover, a significant proportion of the population in developing nations, approximately 70%, currently favors the utilization of herbal remedies as opposed to conventional pharmaceuticals. Garlic is a herbal plant known for its antihypertensive properties. This review specifically examines the current mechanisms by which garlic acts as an antihypertensive, and presents the clinical evidence available to date regarding garlic's effectiveness in lowering blood pressure. The present mechanism by which garlic acts as an antihypertensive agent involves its anti-inflammatory, vasorelaxant, antioxidant, anti-apoptotic effects, enhancement of microbiota activities, and improvement of heart function. The antihypertensive effect of garlic is derived from its organosulfur content. Based on multiple clinical trials, the majority of studies have found that administering interventions in the form of capsules containing garlic or aged black garlic extract leads to a decrease in blood pressure. Garlic has anti-hypertensive effects, especially in the form of aged black garlic extract.